2012
DOI: 10.1371/journal.pone.0051185
|View full text |Cite
|
Sign up to set email alerts
|

Transient Increase in Homocysteine but Not Hyperhomocysteinemia during Acute Exercise at Different Intensities in Sedentary Individuals

Abstract: Considering that hyperhomocysteinemia is an independent risk factor for cardiovascular disease, the purpose of this study was to determine the kinetics of serum homocysteine (tHcy) and the vitamins involved in its metabolism (folates, B12, and B6) in response to acute exercise at different intensities. Eight sedentary males (18–27 yr) took part in the study. Subjects were required to complete two isocaloric (400 kcal) acute exercise trials on separate occasions at 40% (low intensity, LI) and 80% VO2peak (high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 36 publications
7
21
0
Order By: Relevance
“…Deminice et al (2016) also provided evidence that the elevation of tHcy as a consequence of an acute bout of exercise does not cause hyperhomocysteinemia. However, we have previously shown a 26% increase in tHcy (Iglesias-Gutiérrez et al 2012), which could have physiological or clinical relevance.…”
mentioning
confidence: 75%
See 2 more Smart Citations
“…Deminice et al (2016) also provided evidence that the elevation of tHcy as a consequence of an acute bout of exercise does not cause hyperhomocysteinemia. However, we have previously shown a 26% increase in tHcy (Iglesias-Gutiérrez et al 2012), which could have physiological or clinical relevance.…”
mentioning
confidence: 75%
“…The underlying mechanism remains unclear, although our previous data suggest that it could be related to increased energy expenditure (Iglesias-Gutiérrez et al 2012), since the maximal tHcy concentration occurred during exercise. At the same time, we have also showed that it could be related to changes in renal function in response to exercise (Venta et al 2009).…”
Section: R a F Tmentioning
confidence: 95%
See 1 more Smart Citation
“…These authors suggested that the high intensity sustained by the runners comparing to the 100 km run and mountain bike race, can have more rest periods during trials, being a possible answer of this response. In contrast, other research studies including different intensities showed that the tHcy increase is independent of the intensity of the exercise [11,24] or type of exercise [22]. Sotgia et al [21], who compared athletes and non-athletes subjects, found no changes in tHcy after acute exercise but a decrease in the Homocysteine reduced form [21].…”
Section: Acute Effect Of Exercise On Thcy Concentrationsmentioning
confidence: 91%
“…Moreover, it seems that there is some consensus about the increase of folate, vitamin B 12 after acute exercise, competition or training programs [11,46]. Vitamin B 6 is required as coenzyme of transaminases, decarboxylases and glycogen phosphorylase in metabolic pathways of energy production, but in contrast, results from the study of Iglesias-Gutierrez et al [24], did not reported any relationship between vitamin B 6 and substrate utilization during different intensities throughout the trials [24]. On the other hand, Herrmann et al [17], suggest that endurance athletes had a higher prevalence of B vitamin deficiency due to the high necessity of vitamin B 6 and folate not only during exercise but also during training [47] because vitamin B 6 is necessary to fuel working muscles and to repair damaged tissue [5].…”
Section: Implicated Biomarkers Related To Homocysteine Concentrationsmentioning
confidence: 99%